Perceived Value As A Key Variable In Purchase Decisions Beauty Products on The Tiktok - Made Mulia Handayani; Made Ayu Desy Geriadi; Nyoman Dwika Ayu Amrita; Tjokorda Gde Agung WIjaya Kesuma Suryawan (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
The increasingly rapid development of technology has had an impact on the business world, including in the marketing sector. Online marketing is a trend in society today. Many business people market their products through TikTok media by using influencers and creating interesting content. This research aims to test the effect of using Influencers and User Generated Content (UGC) in purchasing decisions for cosmetic products on the Tiktok application with Perceived value as a mediating variable in the people of Denpasar City. The object of this research is consumers of beauty products on the Tiktok application. The population of this research is the people of Denpasar City. The sample used was 96 respondents and a questionnaire as a data collection tool. This research uses the SEM analysis method using outer model, inner model , hypothesis testing and mediation testing. The research results found that the use of influencers and UGC had a positive and significant effect on perceived value. The use of influencers has a positive but not significant influence on purchasing decisions, in contrast to UGC and perceived value which have a positive and significant influence on purchasing decisions. In this research, perceived value was able to mediate the influence of the use of influencers and UGC on purchasing decisions for cosmetic products on the TikTok application.